Joana Vasconcelos: managing an artist’s studio in the early 21st century - Fernandes, A.; Afonso, L. (International Journal of Arts Management, 2014)
Although still relatively young, Joana Vasconcelos is a respected artist on the international contemporary art scene. Her career has included a number of impressive achievements, such as a prestigious solo exhibition at the Palace of Versailles in 2012. Her success belies the romantic view of art and artists in which success is attributed to a combination of luck, talent and improvisation. This study demonstrates that Vasconcelos's management skills are virtually as important as her creativity. Her management and business talents and skills include an ability to work with a top-quality team; delegate tasks and responsibilities; engage in rigorous planning of the production process; maintain diligent communication with the media, collectors and other interlocutors; and cultivate social and institutional relationships with various markets.